2020
DOI: 10.1186/s12920-020-0691-4
|View full text |Cite
|
Sign up to set email alerts
|

The cox-filter method identifies respective subtype-specific lncRNA prognostic signatures for two human cancers

Abstract: Background: The most common histological subtypes of esophageal cancer are squamous cell carcinoma (ESCC) and adenocarcinoma (EAC). It has been demonstrated that non-marginal differences in gene expression and somatic alternation exist between these two subtypes; consequently, biomarkers that have prognostic values for them are expected to be distinct. In contrast, laryngeal squamous cell cancer (LSCC) has a better prognosis than hypopharyngeal squamous cell carcinoma (HSCC). Likewise, subtype-specific prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In North America and Europe, including the United States, Canada and the United Kingdom, the incidence of EAC is high (16). However, in recent years, the morbidity and mortality of EAC in China has shown an increasing trend, which has aroused widespread concern (17)(18)(19). Despite continued advances in its diagnosis and treatment, the prognosis of EAC patients remains poor (20).…”
Section: Discussionmentioning
confidence: 99%
“…In North America and Europe, including the United States, Canada and the United Kingdom, the incidence of EAC is high (16). However, in recent years, the morbidity and mortality of EAC in China has shown an increasing trend, which has aroused widespread concern (17)(18)(19). Despite continued advances in its diagnosis and treatment, the prognosis of EAC patients remains poor (20).…”
Section: Discussionmentioning
confidence: 99%
“…PVT1 is a well-known oncogene and correlated with a variety of cancers according to both the lncRNADisease 2.0 knowledgebase and the GeneCards database [ 121 ]. In our previous study [ 122 ], PVT1 was identified as a subtype-specific prognostic gene for esophageal adenocarcinoma using a feature selection algorithm called the Cox-filter method [ 123 ]. In this study, it was identified as a pan AC discriminative gene, which leads us to anticipate that PVT1 may be more relevant to the AC type than the SCC type, even though PVT1 has also been verified in the literature to associate with the SCC cancer type such as esophageal squamous cell carcinoma [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the pan-AC prognostic lncRNAs, MALAT1 is a well-known oncogene and has been linked to a variety of cancers so far, including non-small cell lung cancer, cervical cancer, tongue squamous cell carcinomas and gastric cancer. In our previous study [ 122 ], it was identified as a subtype-specific prognostic gene for laryngeal squamous cell carcinoma using the Cox-filter method [ 123 ], further implying its possibility of being a pan-cancer lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of transcriptomic data, such as mRNA molecules, has the potential to elucidate the involvement of specific genes in complex diseases [ 11 ], such as heart disease [ 12 ], lung cancer [ 13 , 14 ], and diabetes [ 15 ]. To date, numerous studies have been conducted to identify relevant gene signatures associated with DR, utilizing transcriptomic data and bioinformatics methods [ 16–19 ].…”
Section: Introductionmentioning
confidence: 99%